For the Development of Effective HRM Systems: Inter-Relationships Between HRM Practices Using Correlation Analysis - Uysal, Gurhan (My University, 2012)
The aim of the study described herein was to explore the relationships between the practices of HRM used in organisations, in order to inform the development of effective HRM systems. Our exploratory study assumed that staffing, training, performance evaluation and compensation are the most prominent practices in HRM, and used Snell and Dean's (1992) questionnaire to investigate these practices. Using correlation analysis to characterise the relationships, we identified the signs of the correlations involved, and we thereby identified the significant and positive relationships among the HRM practices studied. Strong, positive and significant correlations were observed among the elements of staffing, training, performance evaluation and compensation. These results are important for understanding the inter-relationships between HRM practices, in order to enhance the effect of HR systems on employee-related organisational outcomes. © 2012 Inderscience Enterprises Ltd.
Keywords: HR System; Individual HRM Practices; Relationship of HRM Practices